Content of the Right to Parental Responsibility: Experiences – Analyses – Postulates (Studies of the Central European Professors’ Network, 2022)
The publication entitled Content of the Right to Parental Responsibility. Experiences – Analyses – Postulates is the result of the work of an international team of researchers convened by the Central European Academy in 2022. The subject of this scholarly reflection by the experts is parental responsibility within the legal systems of Central and Eastern European countries. Individual chapters of this volume provide for an analysis of the titular issue from the perspective of domestic legal frameworks and the case law of the European Court of Human Rights in Strasbourg. While maintaining the autonomy of the researchers and allowing for a free selection of subject matter – characteristic of multi-authored and international studies – the legal analyses presented in this publication focus on the following issues: axiological and constitutional foundations for the protection of parental responsibility; protection of parental authority in the system of legal sources; the concept of a parent; the concept of a child; principles of parental responsibility; the rights and obligations of parents and children resulting from parental responsibility; sexual education children and parental responsibility; detailed issues related to parental responsibility; parental authority in case of divorce; the status of a child not subject to parental responsibility; de lege ferenda postulates.